2010
DOI: 10.1176/appi.ajp.2009.09010118
|View full text |Cite
|
Sign up to set email alerts
|

Specific and Generalized Neuropsychological Deficits: A Comparison of Patients With Various First-Episode Psychosis Presentations

Abstract: Early in their course, cognitive deficits are present in all psychotic disorders but are most severe and pervasive in schizophrenia and least pervasive in bipolar disorder and mania.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
144
3
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 185 publications
(163 citation statements)
references
References 36 publications
14
144
3
2
Order By: Relevance
“…17 The negative association between age and years of education on TMT-A scores is in accordance with the decreased attention and processing speed 17 observed with age and lower general intelligence in patients with first-episode psychosis. 28,56 Our study focused on patients with first-episode schizophrenia to exclude effects due to chronic evolution of the disease. In the present study, patients were untreated or treated for only a few days, thus limiting the possible effects of medication.…”
Section: Discussionmentioning
confidence: 99%
“…17 The negative association between age and years of education on TMT-A scores is in accordance with the decreased attention and processing speed 17 observed with age and lower general intelligence in patients with first-episode psychosis. 28,56 Our study focused on patients with first-episode schizophrenia to exclude effects due to chronic evolution of the disease. In the present study, patients were untreated or treated for only a few days, thus limiting the possible effects of medication.…”
Section: Discussionmentioning
confidence: 99%
“…Zanelli et al 16 confirmed that those with schizophrenia demonstrated pervasive cognitive deficits, while those with bipolar disorder showed few; in particular, the schizophrenic patients showed premorbid cognitive deficits, which were absent in bipolar patients.…”
Section: Patients With First Episode Of Illnessmentioning
confidence: 94%
“…21 At the time of the first psychotic episode in adults, patients with schizophrenia seem to have widespread cognitive impairment compared with controls, while patients with bipolar disorder have much less impairment apparently mainly in scores on tests assessing delayed verbal memory and category fluency. 22 It is noteworthy that onset of a first psychotic episode, whether of schizophrenia or mania, is in many cases coincident in time with cognitive maturation of the prefrontal and parietal cortices.…”
Section: Cognitive Impairment During Development In Schizophrenia Andmentioning
confidence: 99%